Study on the structure of phosphorus-containing zeolite anionic nanoporous materials - G. P. Tsintskaladze; T. M. Sharashenidze; L. G. Eprikashvili; M. G. Zautashvili; T. N. Kordzakhia; M. A. Dzagania (Хімія, фізика та технологія поверхні, 2022)
Phosphates are specific compounds of the composition of living organisms, that play a special role in plant and animal life. The skeleton of most living organisms consists mainly of calcium, sodium, magnesium and other phosphates. Because phosphorus plays an important role in supplying nutrients to the environment, it is central to all forms of life. Therefore, interest in this type of material is great, and the scope of application is enormous, from agriculture to medicine.